Photocatalytic degradation of diisopropanolamine in heterogeneous photo-fenton system - Ramli, R.M. (Trans Tech Publications Ltd, 2014)
Photodegradation of 100 ppm diisopropanolamine (DIPA) was studied employing heterogeneous photo-Fenton system using iron modified TiO2 photocatalyst. A series of Fe/TiO2 photocatalysts were prepared via hydrolysis-hydrothermal and wet impregnation methods. Photocatalysts prepared using wet impregnation method was found to have similar activity under both UV and visible light. Addition of H2O2 during the photodegradation study obviously promoted the COD removal efficiency. When stoichiometric concentration of H2O2 was added, as high as 80 of COD was removed within 1.5 h reaction. Further modification is required to increase the photocatalyst performance in photodegradation of DIPA. Â© (2014) Trans Tech Publications, Switzerland.